2010
DOI: 10.1016/j.mpmed.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

What is type 2 diabetes?

Abstract: Type 2 diabetes is a common metabolic disorder characterized by chronic hyperglycaemia. It is associated with a reduced life expectancy owing to a greater risk of heart disease, stroke, peripheral neuropathy, renal disease, blindness and amputation. At present, the best predictors of increased diabetes risk and progression to diabetes are an elevated fasting plasma glucose, an abnormal glucose tolerance test, obesity and evidence of impaired insulin action. However, the mechanisms by which people with impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 42 publications
0
32
0
6
Order By: Relevance
“…(2) Type 2 diabetes may well be associated with the greatest burden of suffering among obesity-related diseases. (3) …”
Section: Introductionmentioning
confidence: 99%
“…(2) Type 2 diabetes may well be associated with the greatest burden of suffering among obesity-related diseases. (3) …”
Section: Introductionmentioning
confidence: 99%
“…Diabetes melitus tipe 2 merupakan salah satu masalah kesehatan global yang paling meningkat dalam beberapa tahun terakhir (Gosslau et al, 2018). Diabetes Melitus tipe 2 (T2DM) adalah kelainan metabolisme kronis yang ditandai dengan tingginya kadar glukosa dalam darah (Smushkin and Vella, 2010;Nambirajan, 2018). Diabetes dapat memengaruhi berbagai organ sistem dalam tubuh dalam jangka waktu tertentu yang disebut komplikasi.…”
Section: Pendahuluanunclassified
“…6i, 6j, 6k) that were not substrate of NAT2 enzyme, and prodrug 6j (MB07803) also demonstrated potent glucose-lowering effects. A full pharmacokinetic study of MB07803 showed that it has good OBAV: 37% in rats, which showed 2-fold higher improvement over MB06322 (1). Finally, the first-generation compounds MB06322 (1) and its parent MB05032 (2) were compared with MB07803 (6j) -…”
Section: Oral Delivery Of Fbpase Inhibitors With No Nat Liability: Prmentioning
confidence: 99%
“…Hyperglycemia is one of many hallmarks for T2DM, which is associated with an increased risk of nephropathy, vision loss, and heart diseases. 1 Consequently, existing therapies benefit patients by lowering blood sugar levels. Several classes of oral hypoglycemic agents are currently on the market to treat T2DM, including sulfonylureas (e.g.…”
Section: Introductionmentioning
confidence: 99%